Ganoderma Root Rot Mortality: Managing the Growing Threat to the Tree behind Traditional Agroforestry in Indian Arid Region: Ganoderma Root Rot Mortality - Mawar, Ritu; Ranganathan, Saranya (Annals of Arid Zone, 2023)
Last couple of decades have witnessed large-scale mortality of Indian mesquite (Prosopis cineraria (L.) Druce) or Khejri in specific areas of the Indian arid region. It is caused by Ganoderma lucidum, a root rot- causing soil-borne fungi. The disease is more common in sandy soils where trees experience greater moisture and temperature stress during the summers which predisposes them to the fungal infection. The infection spreads from diseased to healthy trees primarily through root-to-root contacts. Movement of injured lateral roots of P. cineraria from infected tree to healthy trees during mechanical ploughing is a common way of infection dissemination. In later stages of infection, the trees weaken and are then often attacked by an insect, Acanthophorus serraticornis, which aggravate the root rot incidence and accelerate the tree mortality. Isolating infected trees from healthy ones by digging a mechanical trench around has been advocated in past as a prophylactic measure. But the scattered distribution of trees in the fields limits adoption of this approach on a large scale and hence alternate approaches need to be developed to minimize the tree mortality. In this paper, we have discussed about symptoms, pathogen, predisposing factors and management strategies of Ganoderma induced tree mortality and also some ongoing studies.